Tinjauan Yuridis Tentang Pencabutan Laporan Tindak Pidana Kekerasan Dalam Rumah Tangga Oleh Korban Terhadap Pelaku - Kadek Desi Lasmini; Elwidarifa Marweny (CV. ITTC INDONESIA, 2025)
Domestic Violence (KDRT) is a social phenomenon that occurs in some households in the world, including Indonesia. Domestic violence often occurs in a family environment that is supposed to be a safe place, but in reality it is a source of violence against children and women. Domestic violence is regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence. However, practices in the field face challenges such as the revocation of domestic violence reports that hinder law enforcement against victims. The formulation of the problems in this study is, 1) How is the legal arrangement of domestic violence in Indonesia, 2) Whether the revocation of the report of the Crime of Domestic Violence by the victim against the perpetrator is in accordance with the concept of justice, and 3) What are the legal consequences that can be caused by the revocation of the report of a domestic violence crime by the victim against the perpetrator. The type of research used in this study is normative juridical with a type of legislative approach and a conceptual approach. The results of this study show that; 1) Law Number 23 of 2004 concerning the Elimination of Domestic Violence is the main legal basis that regulates the protection of victims of violence in the family environment in Indonesia; 2) From the principle of justice, the revocation of domestic violence reports by victims is appreciated because it protects human rights, and for perpetrators, this is a form of restorative justice that provides opportunities to improve oneself and family relationships; 3) The legal consequence caused by the revocation of the report is the dismissal of the prosecution process.